PERCEPTION OF RURAL YOUTH TOWARDS FARMING AS AN OCCUPATION IN PUNJAB - ANJANA RAI * AND KIRANJOT SID, (The Journal of Research ANGRAU, 2022)
The purpose of the research was to study the perception of the 200 rural youth studying inclass 10th/11th/12th aged 14-19 years in Punjab state towards farming as an occupation.Economic, socio-cultural, personal, physical and psychological factors were worked out to measurethe perception of youth towards farming as an occupation. The findings of the study revealedthat nearly three fourth of the respondents (71.5%) perceived that farming was not economicallyprofitable occupation and they were dissatisfied with the income earned from farming. Nearly halfof the sample (49%) agreed that other occupations can be undertaken along with farming asfarming is seasonal and gives enough time to be involved in other subsidiary occupations. Mostof the respondents (91%) agreed that farmers can earn throughout their life as there is noretirement age for farming. Youth (95.5%) also perceived that farming has as a low social statusand it was also considered as physically laborious occupation by 97.5 percent of the respondentsand most of the youth (98%) viewed that farming is associated with health risks due to exposureto heat, cold, dust and chemicals. However, majority (84%) of the youth believed that hard workin farming kept them healthy. More than three fourth of the sample youth (78.5%) dislike farmingand were disinterested. Three fourth of the respondents (75%) were dissatisfied with incomefrom farming as it was insufficient to fulfil their family expenditure.